2020
DOI: 10.1007/s00204-020-02779-2
|View full text |Cite
|
Sign up to set email alerts
|

Hepatotoxic pyrrolizidine alkaloids induce DNA damage response in rat liver in a 28-day feeding study

Abstract: Pyrrolizidine alkaloids (PA) are secondary plant metabolites that occur as food and feed contaminants. Acute and subacute PA poisoning can lead to severe liver damage in humans and animals, comprising liver pain, hepatomegaly and the development of ascites due to occlusion of the hepatic sinusoids (veno-occlusive disease). Chronic exposure to low levels of PA can induce liver cirrhosis and liver cancer. However, it is not well understood which transcriptional changes are induced by PA and whether all hepatotox… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
24
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 29 publications
(25 citation statements)
references
References 27 publications
(34 reference statements)
1
24
0
Order By: Relevance
“…Those three studies indicated a clastogenic potential, which is in line with the different regulators included in the network predicted by IPA, such as BRCA1, ATR, MDC1, MCPH1 and H2AX (Bonner et al 2008 ; Hustedt and Durocher 2016 ). Interestingly, a study on pyrrolizidine alkaloids reported the induction of a DNA damage response involving the up-regulation of Rad51 and Ddias that were also induced our study (Ebmeyer et al 2020 ). For THI or IMZ, no specific networks or evident GO enrichment patterns were observed.…”
Section: Discussionmentioning
confidence: 99%
“…Those three studies indicated a clastogenic potential, which is in line with the different regulators included in the network predicted by IPA, such as BRCA1, ATR, MDC1, MCPH1 and H2AX (Bonner et al 2008 ; Hustedt and Durocher 2016 ). Interestingly, a study on pyrrolizidine alkaloids reported the induction of a DNA damage response involving the up-regulation of Rad51 and Ddias that were also induced our study (Ebmeyer et al 2020 ). For THI or IMZ, no specific networks or evident GO enrichment patterns were observed.…”
Section: Discussionmentioning
confidence: 99%
“…Pyrrolizidine alkaloids (PAs), a group of secondary plant metabolites, belong to the most widely distributed natural toxins [ 1 ]. Intake of PAs present in plants and/or contaminated foodstuffs causes numerous cases of toxicity [ 2 , 3 ].…”
Section: Introductionmentioning
confidence: 99%
“…Intake of PAs present in plants and/or contaminated foodstuffs causes numerous cases of toxicity [ 2 , 3 ]. Tea, honey, and herbal spices were identified as the primary sources contributing to human exposure to PAs [ 1 , 4 , 5 ]. Different doses of PAs could cause acute toxicity and chronic toxicity [ 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, Ebmeyer and colleagues published a 28-day feeding study with six pyrrolizidine alkaloids in rats (Ebmeyer et al 2020 ). Pyrrolizidine alkaloids occur in honey, tea and herbal spices, which represent the main sources of human exposure (Bodi et al 2014 ; EFSA 2017 ; Mulder et al 2018 ).…”
mentioning
confidence: 99%
“…Liver enzymes were not increased in the exposed rats. However, at the highest tested doses, gene array analyses showed clear expression changes (Ebmeyer et al 2020 ). A set of 36 commonly regulated genes was observed for the high-dose groups of four structurally different pyrrolizidine alkaloids.…”
mentioning
confidence: 99%